PERSEPSI GENERASI MUDA TERHADAP PERKEMBANGAN FENOMENA LARI DI KOTA PALANGKA RAYA: ANTARA FOMO DAN KONSTRUKSI IDENTITAS SOSIAL - M Hanif Kurniawan; Vito Yulianto; Tuti Arlina Gea; Herliska Harianja (SOSFILKOM : Jurnal Sosial, Filsafat dan Komunikasi, 2025)
This descriptive qualitative study, using a phenomenological approach, analyzes the perceptions of young people in Palangka Raya City toward the running phenomenon. The main goal is to examine how running serves as a medium for self-identity construction and is influenced by social factors. Informants were drawn from participants in the Sociology, Culture, and Running (Soculrun 2025) event. The findings show that running has transformed into a complex social practice, moving beyond its physical function, and becoming essential in constructing a healthy lifestyle and modern urban self-image. Running activities contribute to forming a collective Habitus, manifested through shared practices and values. The running community is a vital producer and consumer of Social Capital (networks and support) and a significant arena for Self-Identity formation validated by the social environment. Participation also facilitates the acquisition of Cultural Capital (knowledge and skills valued in the community). Although the study notes the presence of FOMO and the risk of over consumption, the youth demonstrate a reflective and selective attitude, adapting the trend to their personal needs for healing or productive leisure. Sociologically, running enhances public space dynamics, promoting orderly social interaction, thus supporting the sustainability of this practice in urban society